Bacterial metataxonomic profile and putative functional behavior associated with C and N cycle processes remain altered for decades after forest harvest. (April 2018) - Mushinski, Ryan M.; Zhou, Yong; Gentry, Terry J.; Boutton, Thomas W.
Abstract: While the impacts of forest disturbance on soil physicochemical parameters and soil microbial ecology have been studied, their effects on microbial biogeochemical function are largely unknown, especially over longer time scales and at deeper soil depths. This study investigates how differing organic matter removal (OMR) intensities associated with timber harvest influence decadal-scale alterations in bacterial community composition and functional potential in the upper 1-m of the soil profile, 18 years post-harvest in a Pinus taeda L. forest of the southeastern USA. 16S rRNA amplicon sequencing was used in conjunction with soil chemical analyses to evaluate (i) treatment-induced differences in bacterial community composition, and (ii) potential relationships between those differences and soil biogeochemical properties. Furthermore, functional potential was assessed by using amplicon data to make metagenomic predictions. Results indicate that increasing OMR intensity leads to altered bacterial community composition and the relative abundance of dominant operational taxonomic units (OTUs) annotated to Burkholderia and Aciditerrimonas ; however, no significant differences in dominant phyla were observed. Genes involved in nitrification were significantly lower in the most intensively harvested treatment, most likely as a result of reduced substrate. Additionally, the relative abundance of genes associated with dissimilatory nitrate reduction and denitrification were highest in the most intensively harvested plots, indicating that the volatilization of N was a potential pathway of N loss in that treatment. Genes associated with glycosyltransferases were significantly reduced with increasing harvest intensity while polysaccharide lyases increased. Additionally, when overall differences in N-cycling genes were observed (0–100 cm), they generally occurred at soil depths below 30 cm, indicating the importance of examining deeper soil horizons when assessing the effect of forest disturbance on soil biogeochemical processes. Highlights: Bacterial community structure at 0–10 cm and 10–30 cm was altered by timber harvest. Gene counts associated with C and N cycling were altered by timber harvest. Differences in N-cycle genes were attributed to soil depths below 30 cm.